Larvae of Hydromanicus (Insecta: Trichoptera: Hydropsychidae) from Thailand - Prommi, Taeng On; Permkam, Surakrai (Zootaxa, 2015)
Larvae of only 2 of the 13 species of Hydromanicus known from Thailand have been described previously. In this research, the “metamorphotype method” was used to associate yet-unidentifiable larvae and pupae with their identifiable adults: Pupal identifications were based on genitalic features in common with described adults, and larvae were associated with the pupae. Herein, the final larval instar of Hydromanicus malayanus, H. abiud and H. inferior are described and illustrated.